Ministry Of Industry, Trade And Small & Medium Projects Decree No. 692 Of The Year 2015 = وزارة الصناعة والتجارة والمشروعات الصغيرة والمتوسطة قرار رقم 692 لسنة 2015 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic